Vegetation Dynamics and Response to Climate Change in Yarlung Tsangpo River Basin During 1981–2020 - Fang Liu; Junlong Tang; Jing Guo; Leilei Zhang; Xuefeng Sang; Weijian Guo; Tianling Qin (Atmosphere)
The ecosystems of the Yarlung Tsangpo River Basin (YTRB) are fragile and sensitive to climate change, so an in-depth analysis of the relationship between the vegetation dynamics in the YTRB and climate change is crucial to understand regional and global climate change. This study quantified the spatial and temporal characteristics of the vegetation cover and meteorological elements in the YTRB over the past four decades. The evapotranspiration data were corrected by combining the characteristics of the vegetation in the region in order to systematically explore the relationship between the vegetation change and climate change response in the YTRB. The results indicated that the fractional vegetation cover (FVC), air temperature (ATEM) and precipitation (PRE) showed a significant increase during 1981–2020, with a variable speed of 0.05/10a, 0.38 °C/10a, and 13.3 mm/10a. The actual evapotranspiration (AET) decreased significantly (32.8 mm/10a). There were positive effects of the increased ATEM and decreased AET on the increase in FVC, with ATEM as the leading factor of influence. After excluding the influence of other factors, the degree of influence of PRE on FVC increased to 2.5 times of the original, and the AET increased by 28.57%. The three climate factors synergistically contribute to the positive development of FVC in 47.43% of the upper and middle sections of the YTRB.